Investigating the sensitivity of health benefits to focussed PM2.5 emission abatement strategies. (December 2015) - Oxley, T.; ApSimon, H.M.; de Nazelle, A.
Abstract: Modelling, pollution monitoring and epidemiological studies all have a role to play in developing effective policies to improve air quality and human health. Epidemiological studies have shown that of particular importance are the effects of fine particulate matter, PM10 and PM2.5 which can penetrate into human lungs. At present it is not clear which components of PM are responsible for health effects although toxicological studies have identified several potential factors. Hence, based on WHO guidance, current legislation has focused on the total mass, with the EC setting limit values on total PM10, followed by target reductions for population exposure to PM2.5 in urban agglomerations. Trends in measured concentrations at selected urban monitoring stations are required as evidence for achievement of these reductions. This paper addresses these issues at the borough level in London using the integrated assessment model UKIAM, developed originally for application at the national scale, with illustrations comparing abatement of two contrasting sources – domestic combustion and road transport. The former, dominated by natural gas generating NOX emissions, contributes to longer range secondary PM formation extending beyond the city. The latter is an important source of black carbon as a primary pollutant causing local exposure, as well as NOX . WHO data is used in relation to impacts of particle concentrations by mass, and response functions for black carbon are taken from the literature. The results show that from a city perspective there are enhanced benefits from reducing the road transport emissions, especially with regard to potential toxicity of black carbon. The scenarios modelled also highlight the spatial variations of benefits across London, and illustrate deviations from trends as represented by limited monitoring data from the different boroughs, together with the influence upon exposure of mobile population within the city. Highlights: We use integrated assessment modelling to focus strategies to benefit human health. We quantify the variable potential for health benefits in different London boroughs. We highlight the greatly increased health benefits of focussing upon black carbon. We discuss the uncertainties in reported health impacts of fine particulate matter. We suggest greater possible benefit under the EC Directive by reducing BC emissions.